Current State, Future Prospect and Challenges on Fungal Biomaterials: A Review - Syafrani, Firyal Zalfa; Dewi, Hammanda Aura; Ginting, Rigo; Witadi, Muhammad Ridhwan Amarullah; Sari, Nastiti Intan Permata; Farah, Nadya (MUNISI: Military Mathematics and Natural Sciences, 2024)
The durability of fungal mycelia as well as its sustainability and environment-friendliness make them of great interest for a wide variety of applications. These include replacing non-degradable plastics in packaging, alternative to animal-based leather in fashion, durable and sturdy interior design, and eliminating CO2 emissions in architecture and building designs. Many well-known companies have implemented these products in their sustainability and environmental campaigns Fungal biomaterials still face challenges in product development, for example, producing non-destructible but functional biomaterials, especially in structural designs. Fungal biomaterials, however, will have many advantages in the future due to an increase in public awareness regarding sustainable and environmentally friendly products.